An accurate geometric distance to the compact binary SS Cygni vindicates accretion disc theory - Miller-Jones, James; Sivakoff, G.; Knigge, C.; Koerding, E.; Templeton, M.; Waagen, E. (The American Association for the Advancement of Science, 2013)
Dwarf novae are white dwarfs accreting matter from a nearby red dwarf companion. Their regular outbursts are explained by a thermal-viscous instability in the accretion disc, described by the disc instability model that has since been successfully extended to other accreting systems. However, the prototypical dwarf nova, SS Cygni, presents a major challenge to our understanding of accretion disc theory. At the distance of 159 ± 12 parsecs measured by the Hubble Space Telescope, it is too luminous to be undergoing the observed regular outbursts. Using very long baseline interferometric radio observations, we report an accurate, model-independent distance to SS Cygni that places the source substantially closer at 114 ± 2 parsecs. This reconciles the source behavior with our understanding of accretion disc theory in accreting compact objects.